2020
DOI: 10.1155/2020/9108216
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Model for Predicting the 5-Year Risk of Type 2 Diabetes in Patients with Hypertension: A Retrospective Cohort Study

Abstract: Background. Hypertension is now common in China. Patients with hypertension and type 2 diabetes are prone to severe cardiovascular complications and poor prognosis. Therefore, this study is aimed at establishing an effective risk prediction model to provide early prediction of the risk of new-onset diabetes for patients with a history of hypertension. Methods. A LASSO regression model was used to select potentially relevant features. Univariate and multivariate Cox regression analyses were used to determine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…The risk variables for T2DM were consistent with prior studies. 2,19,[23][24][25] Studies have suggested that the accumulation sites of body fat are associated with blood glucose levels. [25][26][27] Moreover, WC is a better measure of abdominal obesity than BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The risk variables for T2DM were consistent with prior studies. 2,19,[23][24][25] Studies have suggested that the accumulation sites of body fat are associated with blood glucose levels. [25][26][27] Moreover, WC is a better measure of abdominal obesity than BMI.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 28 Nomogram relies on a user-friendly digital interface to improve accuracy and provide easier to understand prognosis to help better clinical decision-making. 24 , 54 , 55 In this population-based cohort study, we developed and validated an individualized prediction nomogram of 5-year risk of T2D in a non-obese population. To the best of our knowledge, our study is the first to establish an individualized predictive nomogram for predicting the 5-year risk of T2D in a non-obese population.…”
Section: Discussionmentioning
confidence: 99%
“…The key to successful intervention is the early identification of people at high risk of T2D [18]. In recent years, numerous T2D risk prediction models have been developed and tested, such as the Australian Type 2 Diabetes Risk Assessment Tool [23], the Cambridge Risk Score [11], the Finnish Risk Score [13], the Framingham Diabetes Risk Score [24], and among others [25][26][27]. However, there is a lack of a risk prediction model based on cohort study data for the Japanese population, especially for patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%